ANALISIS DIMENSI BERNALAR KRITIS DALAM PROFIL PELAJAR PANCASILA MATERI HAK DAN KEWAJIBAN KELAS IV DI SEKOLAH DASAR - Winda Pujiyanti; Suyoto; Muflikhul Khaq (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research aims to determine and analyze the dimensions of students' critical reasoning in the Pancasila student profile regarding rights and obligations in class IV at SD Negeri 1 Adimulyo. The subjects of this research were 14 grade IV students at SD Negeri 1 Adimulyo. The object of this research is students' critical reasoning abilities. This type of research is descriptive qualitative research with a case study design. Data collection techniques use observation, tests and interviews. Data validity techniques use triangulation of sources and techniques. Data analysis used in this research is data collection, data reduction, data presentation, and verification. The results of this research, in terms of test results, show that students have critical reasoning abilities in the categories of very advanced, proficient, already developing, and starting to develop. This can be explained as follows, the indicator of the ability to obtain information and process ideas with descriptions of being able to meet the indicators in the starting to develop category and not yet meeting the indicators in the very advanced, proficient and already developing categories. Indicators for analyzing and evaluating reasoning with descriptions are able to meet indicators in the categories of very advanced, proficient, and already developed. The indicators for analyzing and evaluating reasoning do not yet meet the indicators in the starting to develop category. Indicators reflect thoughts and thinking processes with descriptions that meet the indicators of being very proficient, proficient and already developed. Indicators reflecting thoughts and thinking processes do not yet meet the indicators in the beginning to develop category.